Evaluation of a reactive agility assessment device in youth pootball Players - Hoffman, J. R. (The Journal of Strength and Conditioning Research, 2020)
The purpose of this study was to examine the reliability and validity of the Blazepod reactive agility device on sport-specific movements in competitive youth football players. Thirty-one male athletes (16.7 ± 1.5 years; 179.4 ± 7.0 cm; 75.0 ± 21.0 kg), all members of a youth tackle football team, volunteered to participate in this study. Subjects performed 3 reactive agility drills (side shuffle reactive agility, 1-m reactive agility, and 3-m reactive agility) at least 72 hours apart. In addition, all subjects also performed 3 traditional agility exercises: proagility, T drill, and L drill. These sessions were part of the offseason conditioning program for the football team that involved sport-specific drills. All assessments occurred following a warm-up and conducted in the same order on each occasion. To assess the validity of the reactive agility drills, the head coach was asked to rank the football playing and agility ability of the players participating in the study. The intraclass correlation coefficient values indicated that all 3 reactive agility drills displayed excellent reliability (r's ranging from 0.833 to 0.884). The measurement error was smaller than the individual variability, indicating that measurement error had a very limited effect on the results. Subjective rankings for agility significantly correlated with each of the agility and reactive agility measurements. Results of this study indicate that the Blazepod reactive agility device is a reliable measure of reactive agility performance and are consistent with the coach's perception of the athlete's agility performance, thus demonstrating construct validity.